Analysis of the synergistic effect for bioactive compound of orthosiphon stamineus and eugeniapolyantha - Nurul Nabillatul Munifa Bt R. Azmi (School of Bioprocess Engineering, University Malaysia Perlis, 2016)
The combination of herbs has drawn much attention of people worldwide, not only because of their economic value as food products, but also for their antioxidant compounds. Orthosiphon stamineus and Eugenia polyantha are examples of herbs with antioxidant properties by their own, but that can be improve when mixed. In the present work, the antioxidant activity and phenolic compounds were from the individual herbs, and from mixtures of these herbs in different extraction method. The total phenolic content and antioxidant compounds were extracted using distilled water at 100 C for decoction method and by using ethanol for soxhlet method. The extracts were then evaluated using Folin-Ciocalteu reagent for their total phenolic content and 2, 2-Diphenyl-1-picrylhydrazyl hydrate (DPPH) assay for their antioxidant compounds. Further analysis was done using High Performance Liquid Chromatography (HPLC) to verify the gallic acid existence in the extracts. Mixture herbs > Eugenia polyantha > Orthosiphon stamineus was the order observed for antioxidant capacity, which can be related to their different composition in phenolic compounds. It was found mixture herbs showed the highest content of total phenolic compounds (2.11 0.09 and 1.88 0.03 mg gallic acid equivalent (GAE) per 20 g of sample) with the antioxidant capacity 0.617 and 0.517 mg ascorbic acid equivalent (AAE) per 20 g of sample for decoction and soxhlet extraction method respectively. This study show that it is possible to commercialize the study of herbs combined in decoction extracts of mixture Orthosiphon stamineus and Eugenia polyantha.